Penerapan Pendidikan Humanisme dalam Perspektif Pendidikan Agama Islam - Herwina Damayanti; Tajudin Nur; Yayat Herdiana (AS-SABIQUN, 2022)
Humanism education or education that requires a humane attitude. This is because humanization must be instilled in humans from an early age so that it becomes a good and fair practice. If humanism is embedded in their daily actions, then not all of their actions cause problems in society. Thus, humanism education becomes an inseparable unit. This article aims to define the application of humanism education in the perspective of Islamic religious education, because the most important thing about Islamic education is the process of activities that improve and perfect the abilities of each individual and increase literacy in the world of education in Indonesia. This article uses a descriptive method with a qualitative approach. The result of this article is that the application of humanism education in the perspective of Islamic religious education is an essential education. Humanism in Islam can be studied by linking the essence of religion with human values. Humanism education is in line with the goal of Islamic education to empower humans to humanize other humans.